Diagnosis and treatment of cryptosporidiosis and giardiasis in cats and dogs in the United States - Scorza, Andrea Valeria, author; Lappin, M. R., advisor; Twedt, David C., committee member; Bachand, Annette M., committee member; Jensen, Wayne A., committee member (Colorado State University. Libraries, 2007)
The first two chapters of this dissertation review the organisms Cryptosporidium species and Giardia species, emphasizing the information most pertinent to dogs and cats. The research work described in chapters 3-9 focused primarily on the diagnosis and treatment of these 2 infectious agents in dogs or cats. In Chapter 3, a monoclonal antibody-based immunofluorescence assay (IFA) was used to detect of Cryptosporidium species oocysts and Giardia species cysts in feces from cats and dogs. The Cryptosporidium IFA results were compared to those of a polymerase chain reaction assay (PCR), and a molecular and phylogenetic analysis on the 18S rDNA and heat shock protein-70 genes were performed on some of the Cryptosporidium positive samples. It was shown that the PCR assay was more sensitive than IFA for the detection of Cryptosporidium species, and that cats and dogs tested in this study were commonly positive for both organisms. Genotype differentiation from the 18S rDNA fragment was not possible, so a PCR- Restriction Fragment Length Polymorphism (RFLP) that comprised a larger and polymorphic fragment of the 18S rDNA gene was performed and described in Chapter 4. Two hundred and ninety two samples were assayed, of which 179 were feline samples and 113 were canine samples. All the feline isolates with adequate DNA for study were C. felis and all the canine isolates were C. canis. In Chapter 5, G. duodenalis isolates of dogs and cats were characterized at the β-giardin and at the glutamate dehydrogenase genes by PCR-RFLP and by sequencing analysis. Thirty six dog samples and 2 cat samples were analyzed. Among the dog isolates 32 corresponded with the restriction pattern of assemblage D and 4 with the assemblage C pattern by the β-giardin analysis. The two cat samples analyzed were typed as assemblage A. In Chapter 6, the clinical management of four cats and a dog with chronic diarrhea and Cryptosporidium and Giardia co-infection is described. Different protocols utilizing metronidazole, fenbendazole, nitazoxanide, tylosin, azithromycin and paromomycin were tried in each individual patient with variable results. However, clinical disease ultimately resolved in each case. The study emphasizes the difficulties in management of these parasites in some patients. In Chapter 7, three experiments are described that were designed to determine the optimal protocol for use of febantel, pyrantel, and praziquantel (FPP) for the treatment of giardiasis in experimentally-infected kittens. When, the United States formulation of FPP was administered at two small dog tablets/cat (approximately 56 mg/kg of febantel per cat), PO, for 5 days was administered to six cats, a significant decrease in cyst shedding and in the percentage of positive samples was observed in the treated group in comparison to the untreated group. In Chapter 8, 26 laboratory cats were inoculated with a Giardia isolate from a cat with chronic diarrhea. The cats that became infected were then administered metronidazole benzoate (25 mg/kg, PO, q12hr for 7 days) to assess the effect on cysts shedding. All the cats became negative for Giardia by IFA and clinical signs of drug toxicity were not detected during the study and so it was concluded that this protocol was safe and effective for the treatment of cats with giardiasis.